Art 36 Basel : Art Unlimited - Lamunière, Simon; Messe, Basel (Basel : Messe Basel, 2005)
Abramovic, Marina ; Aitken, Doug ; Antille, Emmanuelle ; Artschwager, Richard ; Attia, Kader ; Bayrle, Thomas ; Bismuth, Pierre ; Bock, John ; Boltanski, Christian ; Braun, Matti ; Buren, Daniel ; Cabrita Reis, Pedro ; Cardiff, Janet ; Bures Miller, George ; César, Filipa ; Charlton, Alan ; Creed, Martin ; Dahlberg, Jonas ; de Maria, Walter ; Dion, Mark ; Estève, Lionel ; Euba, Jon Mikel ; Faustino, Didier Fiuza ; Finch, Spencer ; Fries, Pia ; Frize, Bernard ; Garaicoa, Carlos ; Gaskell, Anna ; Grayson, Richard ; Grimonprez, Johan ; Grönlund, Tommi ; Nisunen, Petteri ; Guzman, Federico ; Hakansson, Henrik ; Hatakeyama, Naoya ; Hofmann, Hanspeter ; Hubbard, Teresa ; Birchler, Alexander ; Plenge Jakobsen, Henrik ; Kapoor, Anish ; Kogler, Peter ; Kosuth, Joseph ; Larsson, Annika ; Lavier, Bertrand ; Lee Bul ; Long, Richard ; Luser, Constantin ; Moerman, Jean-Luc ; Mori, Mariko ; Motti, Gianni ; Nashat, Shahryar ; Nicolai, Olaf ; Puppi, Daniele ; Pylypchuk, Jon ; Rosefeldt, Julian ; Schiess, Adrian ; Schlick, Jörg ; Schneider, Anne-Marie ; Schulze, Andreas ; Solano, Susana ; Sterbak, Jana ; Stockholder, Jessica ; Tan, Fiona ; The Atlas Group ; Su-Mei Tse ; Turrell, James ; van Lieshout, Erik ; van Warmerdam, Marijke ; Velten, Till ; Viola, Bill ; Walker, Kara ; Wetzel, Markus ; Yass, Catherine ; Zaugg, Rémy ; Atelier van Lieshout ; Donnelly, Trisha ; Kaprow, Allan ; Monk, Jonathan ; Niscino, Tazro ; Othoniel, Jean-Michel ; Pernice, Manfred ; Steiner, Gerda ; Lenzlinger, Jörg ; Tunga
Biog., tent. per kunstenaar
Publication on the occasion of the exhibition 'Art Unlimited at the Messe in Basel, 15.06.2005 - 20.06.2005
boek